Imperial Zions : religion, race, and family in the American west and the Pacific - Hendrix-Komoto, Amanda (Studies in Pacific worlds., 2022)
Imperial Zions explores the importance of the body in Latter-day Saint theology through the faith's attempts to spread its gospel as a ""civilizing"" force, highlighting the intertwining of Latter-day Saint theology and American ideas about race, sexuality, and colonialism.